Loughborough Antennas &Amp; Propagation Conference (LAPC 2017) 2017
DOI: 10.1049/cp.2017.0308
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of log-periodic dipole antenna with LTE band-rejection

Abstract: This study presents an optimized design of a 10-dipole logperiodic antenna for UHF TV reception with LTE band rejection. The simulation of the antenna was performed in CST simulation software followed by optimization of the design using TRF (Trusted Region Framework) algorithm in the frequency range of 450 MHz-900 MHz. The parameters optimized are S11, realized gain and front-to-back ratio of the antenna. TV reception passband is 450 MHz-790 MHz and LTE band is 810 MHz-900 MHz. The proposed antenna design prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The selection of appropriate antenna optimization parameters not only provides promising results, but it also reduces optimization time. Similar to this approach, an optimization of a 10-dipole log-periodic dipole antenna using TRF algorithm was presented in [27], where only the lengths of the first four dipoles were taken into consideration in order to optimize the antenna performance in the UHF TV reception band (470 MHz to 790 MHz) and rejecting long-term evolution mobile service (LTE 800 MHz) band.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of appropriate antenna optimization parameters not only provides promising results, but it also reduces optimization time. Similar to this approach, an optimization of a 10-dipole log-periodic dipole antenna using TRF algorithm was presented in [27], where only the lengths of the first four dipoles were taken into consideration in order to optimize the antenna performance in the UHF TV reception band (470 MHz to 790 MHz) and rejecting long-term evolution mobile service (LTE 800 MHz) band.…”
Section: Introductionmentioning
confidence: 99%
“…This unconventional design of the LPDA was optimized by using a much longer than usual first dipole. On the contrary, an optimized 10-dipole log-periodic dipole antenna has been proposed in [11], which provides good band stop characteristics after 790 MHz, without using external filters, in addition, to avoiding intereference from LTE-band from all the angles. This initial design suggested that in order to achieve LTE rejection characteristics in the higher frequency band of the bandwidth, the dimensions of the shorter dipole could be adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…This initial design suggested that in order to achieve LTE rejection characteristics in the higher frequency band of the bandwidth, the dimensions of the shorter dipole could be adjusted. Motivated by the initially optimized design proposed in [11], this paper presents an optimized version of this LPDA, by optimizing the first three dipoles of the LPDA and the spacing between them only, instead of considering all the dipoles of the antenna. The antenna proposed in this paper achieves better matching, better LTE rejection and a maximum of flatter realized gain compared to the antenna design in [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Log-periodic dipole array geometry and σ is a spacing factor constant defined by where L n and d n are respectively the length and the diameter of the nth dipole, while s n is the spacing between the nth dipole and its consecutive (n + 1)th dipole.The dipoles are connected to the feeding line in such a way that a phase reversal is obtained in the feeding between two consecutive dipoles [7]. In some LPDA designs, constant diameter dipoles are used to reduce cost [8].…”
Section: Introductionmentioning
confidence: 99%